Contextual Bias in Verbal Credibility Assessment: Criteria‐Based Content Analysis, Reality Monitoring and Scientific Content Analysis. Issue 1 (29th October 2013) - Bogaard, Glynis; Meijer, Ewout H.; Vrij, Aldert; Broers, Nick J.; Merckelbach, Harald
Summary Verbal credibility assessment encompasses several methods used to evaluate the credibility of statements by examining their content. In two experiments, we tested to what extent these methods are sensitive to contextual bias. Four statements were presented, although their context was manipulated by confronting raters with extra‐domain information that either enhanced or diminished the credibility of the statements. In Experiment 1, 32 police officers analysed the statements using scientific content analysis. In Experiment 2, 128 undergraduates analysed the statements using criteria derived from criteria‐based content analysis, reality monitoring or scientific content analysis. Results showed that all three methods were equally vulnerable to contextual bias. Copyright © 2013 John Wiley & Sons, Ltd.